Knockout in pif14 induces interruptions in starch synthesis, affecting seed formation and development of rice plants - Alencar, Vicente Thiago Candido Barros (2023)
Light is crucial for the growth and development of plants through their photoreceptors (Cryptochrome - CRY, phototropin - PHOT and phytochrome - PHY) responsible for its uptake and signalling in various mechanisms of biological routes. Therefore, phytochromes play a crucial role in response to light (Photomorphogenesis) and dark (Skotomorphogenesis). Phytochrome is a chromoprotein synthesized in the cytosol as an insoluble protein in its inactive form (Phy-r) when absorbing light in the far-red spectrum (Fr) undergoes a conformation and changes to its active form (Phy-Fr). Once in the active form, Phy migrates to the nucleus where it interacts with PHYTOCHROME TRANSCRIPTION FACTORS (PIFs) triggering various physiological responses in plants. In Arabidopsis Thaliana, 8 isoforms of PIFs (1 – 8) are known and characterized and in rice plant (Oryza Sativa L.) 6 from the alignment of base pairs of PIF3-Like from Arabidopsis, therefore, they are called PILs (11 – 16). We have previously observed that PIF14-knocked rice plants exhibit several physiological disturbances such as reduced germination and grain filling. With this, we hypothesize that PIF14 deficiency can reduce seed quality by reducing starch synthesis, making these seeds less viable. Furthermore, in the next generations, these seeds will induce disturbances in some stages of development. To test this hypothesis, rice plants were knocked out in PIF14 (CRISPR/Cas9 technique) and grown throughout their development cycle. Transformed plants showed a reduction in tillering and panicle growth rates throughout the growing season. Seeds showed lower growth rates associated with reductions in number, size, and mass. Starch accumulation rates were similar showing strong reductions in content at the end of maturation while sucrose and total soluble sugars showed an inverse trend, as did proteins. Seeds showed lower viability indicated by the electrolyte leakage rate and reduced germination rate. In addition, these seeds showed lower seedling establishment, root and shoot elongation rates, associated with delayed vegetative and reproductive development. These results show that knockout of the PIF14 gene affects rice development, probably starting with seed formation via starch metabolism.